Value Addition for Technology Start-Ups Through Physical Co-Location - Venkat, Radhika; Gupta, Amit; Banerjee, Jayanta; Chellappan, Ramesh Babu (Prabandhan: Indian Journal of Management, 2021)
Numerous economic theories, knowledge, social, and communication theories have extensively explored the phenomenon of ‘physical co-location’ in various contexts. However, limited scholarly attention has been given to co-location in emerging contexts such as co-working spaces, predominantly used by start-ups. One of the critical questions examined is how co-location adds value to technology start-ups in the early and growth stages of their development. We chose a premium coworking space in Bangalore, India’s start-up capital, as the study’s research setting during January – March 2020. The qualitative research employed semi-structured interviews to explore the phenomenon. Our findings revealed that start-ups actively used co-located resources to explore, experiment, and validate new business ideas in the early stage. As they transitioned into the growth phase, they exploited co-located industry networks to expand into new markets. They also learned vicariously from other co-located resources and used them to solve complex problems and refined their processes and routines. As start-ups begin to grow and expand, co-location infrastructure-related costs are not justifiable, operations are less secure, and the meta culture of the co-located environment is in conflict with the firm’s operating culture. The results of this study have the potential to be significant for technology start-ups that are exploring new ways of working and addressing uncertainties during the early and growth stages of their development.